Criminal Network Community Detection Using Graphical Analytic Methods: A Survey - Sangkaran, Theyvaa; Abdullah, Azween; JhanJhi, NZ. (EAI Endorsed Transactions on Energy Web, 2020)
Criminal networks analysis has attracted several numbers of researchers as network analysis gained its popularity among professionals and researchers. In this study, we have presented a comprehensive review of community detection methods based on graph analysis. The concept of community was vividly discussed as well as the algorithms for detecting communities within a network. Broad categorization of community detection algorithms was also discussed as well as a thorough review of detection algorithms which has been developed, implemented and evaluated by several authors in social network analysis. Most importantly, a strict review of researches based on the detection of a community in a criminal network was carried out revealing the strength and limitations of criminal network community detection methods. Thus, it becomes obvious through this study that more research activities is necessary and expected in order to further grow this research area.
Keywords: Community Detection; Criminal Network; Graph Analysis; Investigation; Social Network Analysis